Influence on spatial variability on whole life management of reinforced concrete bridges - Kenshel, Omran Mohamed (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2009)
The number of deteriorating bridges due to chloride-induced corrosion increases annually as does the cost of inspection, maintenance, repair and where necessary replacement. Meanwhile, budgets made available to bridge owners/managers for repair and maintenance of these bridges are reducing. To optimise and manage their budget spend, bridge owners/mangers need to rely more on rational decision making methods rather than on subjective engineering judgment. In this thesis, the author has developed a probabilistic- based model which aims to predict the lifetime performance of Reinforced Concrete (RC) structures exposed to chloride corrosive environment and consequently to optimise their lifetime management.
Keywords: Civil and Structural Engineering, Ph.D.; Ph.D. Trinity College Dublin